Pelatihan Komunikasi Efektif bagi Guru - Guru BK SMA di Wilayah Kota Depok, dengan Tema “Membangun Komunikasi Efektif dengan Siswa / Remaja Kekinian" - Wulan Furrie (Jurnal Komunitas : Jurnal Pengabdian kepada Masyarakat, 2019)
The strength of a teacher in teaching is heavily influenced by the effective communication practiced by Dikelas-kelas. Learners are so cool with every word and story that the teacher developed. They are as stunted in the strains of beautiful melodies that splash. While this is the teaching of the teacher, the learners have the convenience of capturing it. Effective communication is very important for the learning process, because as a process where the existence of students with diverse cultures, family background and differences of viewpoints and self-stability are still vulnerable will determine The success of communication itself. The success of communication in the teaching and learning process is not only determined by the teachers but also the mental readiness condition in the teaching-learning process, as well as will be supported by environmental conditioning and Management of the school itself. There is a wide range of breakthroughs in improving communication skills for BK teachers, because BK teachers have the duties, responsibilities, and authority in the implementation of tutoring and counseling services for learners. Related to the student's self-development that suits the needs, potential, talents, interests, and personality of students at school/Madrasah.To improve students ' learning performance, BK teachers are required to create a conducive situation and encourage students to learn more optimally both in independent learning and in class learning with enthusiasm. In order to learn to teach more communicative, there is also necessary proximity between master BK and students as an effort to establish a trust between the two. As a manifestation and concern for the communication process that occurred in the school between the BK teachers and high school students in Depok, then the STIAMI Institute conducts effective communication training for the teachers of BK SMA. With the aim of building and improving the communication skills of master BK to support the process of teaching more effectively through communication. The target audience of this dedication is the teachers of BK SMA in Depok. The cost of devotion is obtained from the Department of Communication in the STIAMI Institute in 2015. The event was held on 20 December 2016 at the STIAMI II campus on JL. Arif Rahman Hakim No. 3 Beji Depok, followed by 50 teachers of BK SMA. From the results of the evaluation of the results and benefits of this dedication activities include improving the communication skills of the BK SMA teachers in understanding students in the face of the learning process according to their age and "kinship". The participants were enthusiastic and actively participated in this training activity. This training is to be done on a wider target and the material can be developed on teachers other than BK teachers. Thus, it is hoped that someday help BK teachers and other teachers to develop and improve the quality of Communication to the students, so that the quality of learning is increased because it has awakened trust between teachers and students in the area of Depok.